Bibliographie Rabelaisienne : Les éditions de Rabelais de 1532 à 1711. Catalogue raisonné, descriptif et figuré - Plan, Pierre-Paul, (European History and Culture - Book Archive pre-2000., 1965)
168 entries (133 in the corpus and 35 in the appendix) described in great detail.